Les ottomans et le temps - Georgeon, François.; Hitzel, Frédéric. (The Ottoman Empire and its Heritage, 2012)
In recent years, there has been an increased interest in the study of the concept of time in the Ottoman Empire. Many existing studies focused on the technical aspects, e.g. the measure of time, and the instruments to do this (like clepsydras, water clocks, hourglasses, and sundials found on the facades of mosques and medreses). Other aspects were neglected, like the various Ottoman experiments with time and the Ottomans' conceptions of time. This collective volume addresses several of these forgotten aspects of the political, social and cultural modalities of time in the Ottoman Empire.